2019
DOI: 10.1111/jcmm.14220
|View full text |Cite
|
Sign up to set email alerts
|

miR‐181c‐5p mediates simulated microgravity‐induced impaired osteoblast proliferation by promoting cell cycle arrested in the G2 phase

Abstract: Impaired osteoblast proliferation plays fundamental roles in microgravity‐induced bone loss, and cell cycle imbalance may result in abnormal osteoblast proliferation. However, whether microgravity exerts an influence on the cell cycle in osteoblasts or what mechanisms may underlie such an effect remains to be fully elucidated. Herein, we confirmed that simulated microgravity inhibits osteoblast proliferation. Then, we investigated the effect of mechanical unloading on the osteoblast cell cycle and found that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…To our knowledge, an increase in apoptosis has never been described in fibroblasts cultured in real or modeled µg, and we did not observe necrosis and/or apoptotic bodies in fibroblast cultures (see Figure 7). Sun et al [51] reported that µg-induced reduction in osteoblast proliferation is because of an arrest in cell cycle progression. In agreement with Sun, in experiments on fibroblasts cultured in µg, modeled by a rotating cell culture system (RCCS), we found a temporary arrest of the cell cycle, with repercussion on proliferation (data not yet published).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, an increase in apoptosis has never been described in fibroblasts cultured in real or modeled µg, and we did not observe necrosis and/or apoptotic bodies in fibroblast cultures (see Figure 7). Sun et al [51] reported that µg-induced reduction in osteoblast proliferation is because of an arrest in cell cycle progression. In agreement with Sun, in experiments on fibroblasts cultured in µg, modeled by a rotating cell culture system (RCCS), we found a temporary arrest of the cell cycle, with repercussion on proliferation (data not yet published).…”
Section: Discussionmentioning
confidence: 99%
“…First, miR-181c-5p, which relates to postmenopausal osteoporosis and fracture risk in diabetic patients, (13,15,35) inhibits osteoblast proliferation in simulated microgravity-settings through interactions with cyclin B1. (36) Here, we could experimentally validate the interaction between miR-181c-5p and PLS3. Second, miR-203a-3p is reported to regulate osteoblast differentiation through repressing DLX5 and RUNX2 in traumatic heterotopic ossification and in bone lesions of metastatic breast cancer, (37)(38)(39) and to inhibit osteogenesis in diabetic rats' jaw bones.…”
Section: Discussionmentioning
confidence: 92%
“…The microgravity-induced decrease in cell proliferation was also seen in other cell phenotypes [22,32,48,49]. However, there are controversial evidences about the effects of microgravity on cell growth in stem cells and cardiomyocytes differentiating from pluripotent stem cells [50][51][52][53][54]. These introduce the hypothesis that the effects induced by microgravity are not only phenotype-dependent but also dependent on the functional and metabolic status of the cells tested.…”
Section: Discussionmentioning
confidence: 99%